Model Concept Attainment To Enriching Students’ Vocabulay Mastery By Using Integrated Reading Book As A Leraning Media During The Covid-19 Pandemi - Wawat Srinawati (Jurnal Serambi Ilmu, 2024)
This research is qualitative research. The objective of this research is to investigated model concept attainment by using Integrated reading toward students’ vocabulary mastery. The writer wanted to know how model concept attainment by using integrated reading can enrich students’ vocabulary mastery. In this research there are 15 sample at fifth semester of STKIP Muhammadiyah, Bogor. The data collecting technique used by the writer are observation, interview and documentation. The documentation attached while the students learn English using integrated book in the classroom. Then, the writer gave question in learning process after the students finished reading integrated book to find out the students’ vocabulary mastery is getting richer or not. Actually the result is positive, all students’ vocabulary is richer. After that, the writer gave interview, this interview did to investigated deeper about the students’ vocabulary mastery when model concept attainment by using integrated reading book in learning English. The result of this study can be concluded that the model concept attainment by using integrated book as learning media is very effective in enriching students’ vocabulary mastery. Furthermore, it can be alternative for the teacher to teach vocabulary mastery and can help the students to easier in learning English.